2017
DOI: 10.1159/000477581
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Activity of Macaca assamensis in Wild and Semi-Provisioned Groups in Shivapuri Nagarjun National Park, Nepal

Abstract: Studying the behavioural flexibility and adaptability of macaques to different habitats is one approach to designing a conservation plan. To determine the activity budget and feeding behaviour and evaluate the effects of seasonality in wild and human- altered habitats of Assamese macaques (Macaca assamensis), we conducted this study in the Nagarjun forest of Shivapuri-Nagarjun National Park (SNNP) in central Nepal. We also updated the list of plant food items of Assamese macaques in the SNNP. Using scan and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Interestingly, some urban-dwelling populations have been shown to spend more time resting and engaging in social activities compared to less urban groups (Saj et al, 1999;El Alami et al, 2012;Jaman & Huffman, 2013;Koirala et al, 2017;Ilham et al, 2018;Thatcher et al, 2019). This suggests a potentially positive effect (rather than negative) of anthropogenic factors on animals' time budgets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some urban-dwelling populations have been shown to spend more time resting and engaging in social activities compared to less urban groups (Saj et al, 1999;El Alami et al, 2012;Jaman & Huffman, 2013;Koirala et al, 2017;Ilham et al, 2018;Thatcher et al, 2019). This suggests a potentially positive effect (rather than negative) of anthropogenic factors on animals' time budgets.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in areas degraded by human activities, animals might be forced to increase their travel time, thereby decreasing their resting and social time, either in order to avoid humans or because natural food sources become scarce (red deer, Cervus elaphus: Grover & Thompson, 1986;lion-tailed macaque, Macaca silenus: Menon & Poirier, 1996;tonkean macaque, Macaca tonkeana: Riley, 2007). In contrast, other studies reveal that animals that live and thrive in an anthropogenic environment tend to spend more time resting and socializing than groups living in less anthropogenic areas (e.g., vervet monkey, Chlorocebus pygerythrus: Saj et al, 1999;Thatcher et al, 2019;Barbary macaque: El Alami et al, 2012;rhesus macaque: Jaman & Huffman, 2013; assamese macaque, Macaca assamensis: Koirala et al, 2017;long-tailed macaque: Ilham et al, 2018). Such beneficial effects may be due to reliance on anthropogenic foods that tends to be higher in calories, more abundant, and more digestible than natural foods (Forthman-Quick, 1988;Rode et al, 2006;Riley et al, 2013;McLennan & Ganzhorn, 2017), and researchers argue that in this condition animals can spend less time feeding, and consequently increase their time spent resting and/or socializing (Jaman & Huffman, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Studying the behavioral flexibility and adaptability of wild and human-altered habitats of Assamese macaques (M. assamensis) in the in central Nepal also showed that provisioning alters the activity and feeding behavior of macaques. Moreover, it can increase human-macaque conflict and disease transmission (Koirala et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Both species are seasonal breeders, and rhesus and Assamese macaque females give birth from April to July and from March to July, respectively (Ogawa, unpublished data). Compared with the rhesus macaque, however, the Assamese macaque is more arboreal, frequently staying in the higher canopy and on cliffs, has a larger body, is less kin biased, and has a more relaxed dominance style (Balasubramaniam et al, 2018;Koirala et al, 2017;Zhou et al, 2014).…”
Section: Study Site and Animalsmentioning
confidence: 99%